Politik Dinasti dalam Perspektif Al-Qur’an - Miftahuddin Miftahuddin; Suhaimi Suhaimi (Madania: Jurnal Ilmu-Ilmu Keislaman, 2019)
Politics and Power entice many people that make them give their great effort to be the one who hold the power. However, according to Ibnu Khaldun, this authority leads the leader become authoritative and tends to be the one and only leader. Besides, the characteristic of the power may also tends to bring about power abusement and misusefulness and unfair treatments.